A Project Report On Influence of Control Surfaces In Aircraft Wing Control Reversal Problems FEA and CED Analysis - NAGARAJA B L (2012)
INTERNAL GUIDE : Nishanth P EXTERNAL GUIDE: Gupta S C USN NO : 1MJ09MAE06 CARRIED OUT AT : Mvj College Of Engineering Bangalore-560067 ACC NO : AE23
Keywords: Influence of Control Surfaces